2014
DOI: 10.1016/j.jcrysgro.2014.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Ga-assisted growth of GaAs nanowires on silicon, comparison of surface SiOx of different nature

Abstract: a b s t r a c tPhysical properties of surfaces are extremely important for initiation and nucleation of crystal growth, including nanowires. In recent years, fluctuations in surface characteristics have often been related to unreproducible growth of GaAs nanowires on Si by the Ga-assisted method. We report on a systematic study of the occurrence of GaAs nanowire growth on silicon by the Ga-assisted method for different kinds of silicon oxides: native, thermal and hydrogen silsesquioxane (HSQ). We find that suc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 44 publications
(64 reference statements)
2
51
0
2
Order By: Relevance
“…Dimerization of two Ga adatoms at the rate K 3 will subsequently lead (with a certain probability) to the nucleation of Ga nanodroplets and ultimately nanowires. Both processes are expected to be associated with the formation of 'craters' or even the openings penetrating through the oxide toward the substrate surface [29,33,34]. Therefore, the rate constants K 3 and K 35 should be orders of magnitude lower than that given by the effective Ga diffusivities (σ 3 D 3 and σ 35 D 3 , with σ as the corresponding capture coefficients [35][36][37]).…”
Section: The Modelmentioning
confidence: 99%
“…Dimerization of two Ga adatoms at the rate K 3 will subsequently lead (with a certain probability) to the nucleation of Ga nanodroplets and ultimately nanowires. Both processes are expected to be associated with the formation of 'craters' or even the openings penetrating through the oxide toward the substrate surface [29,33,34]. Therefore, the rate constants K 3 and K 35 should be orders of magnitude lower than that given by the effective Ga diffusivities (σ 3 D 3 and σ 35 D 3 , with σ as the corresponding capture coefficients [35][36][37]).…”
Section: The Modelmentioning
confidence: 99%
“…18,19,24−30 However, to date, full control over nanowire orientation was observed to be dependent on the wafer batch. 31,32 Most studies focus on the comprehension of the growth at the steady state. To the best of our knowledge, very little work has targeted the understanding of the initial steps of growth.…”
mentioning
confidence: 99%
“…It also indicates a change in the nature of the oxide. 36,37 In order to further illustrate the change in the nature of the native oxide and to relate it to what one generally observes in nanowire growth, 32 we look at the contact angle of the Ga droplets, β (Figure 3). By progressively increasing the native oxide thickness (0.4, 0.6, 0.9, 1.1, 1.2, and 1.5 nm) the contact angle increases from 50°up to ∼120°(see, respectively, Figure 3a−f).…”
mentioning
confidence: 99%
“…The increase of the NW density is associated with the increase of the pinhole density, which can be controlled by the reduction of the oxide layer thickness [116]. But if the oxide thickness is too thin or even oxide free, it will lead to the 2D epitaxial growth such as clusters or thin film, rather than NW growth [122,123]. It is also suggested that the increase of NW density can be achieved by increasing the mask surface roughness [114,123].…”
Section: Influence Of the Substrate And Its Preparationmentioning
confidence: 99%